2013
DOI: 10.1111/1748-5967.12039
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the CNS ganglia in the geometric spider Nephila clavata (Araneae: Nephilidae)

Abstract: As web spiders usually hang with their head downward, geometrical differences in body position could affect the organization of their central nervous system (CNS). Nevertheless, most of our knowledge of spider's CNS is dependent on what has been revealed from wandering spiders. To fill the gap, we describe here the fine structural organization of the ganglionic neurons and nerves in the geometric orb web spider Nephila clavata. Nerve cells in the supraesophageal ganglion in N. clavata are packed in the frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 30 publications
(58 reference statements)
1
25
0
Order By: Relevance
“…Recently there has been a renewed interest in the otherwise neglected area of spider neurophysiology with a number of anatomical studies on brain size and structure (Quesada et al, 2011;Park et al, 2013). Similar methods could be used to compare structures in the supraesophageal ganglion between spiders with extensive site exploration to spiders with hardly any, such as the Darwin's bark spider (Gregoric et al, 2011), in order to estimate the possible computational requirements of the behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently there has been a renewed interest in the otherwise neglected area of spider neurophysiology with a number of anatomical studies on brain size and structure (Quesada et al, 2011;Park et al, 2013). Similar methods could be used to compare structures in the supraesophageal ganglion between spiders with extensive site exploration to spiders with hardly any, such as the Darwin's bark spider (Gregoric et al, 2011), in order to estimate the possible computational requirements of the behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Volumetric measurements, however, failed to find any differences in relative size of the central body between the orb-web spider Nephila clavipes and three web-less spiders (Weltzien and Barth, 1991). Nonetheless, the central body remains at present the most likely candidate for the brain structure that governs web-building behaviour (Park et al, 2013). This is supported by older studies on the orb-web spider Araneus diadematus displaying disruption to normal webbuilding behaviour after its protocerebrum was damaged with laser light (Witt and Reed, 1964;Witt, 1969).…”
Section: The Spider Brain and Behavioural Limitationsmentioning
confidence: 88%
See 1 more Smart Citation
“…The central nervous system of Poecilotheria and Argiope aurantia (Lucas) was described in detail by Babu (1965, 1969, 1975). It was also investigated by Babu and Barth (1984), Wegerhoff and Breidbach (1995), Barth (2002), Hwang and Moon (2003), Hill (2006), Park and Moon (2013), and Park et al (2013). The central nervous system of spiders can be described as a highly condensed organ consisting of two parts: the supraoesophageal ganglion (brain) and the fused suboesophageal ganglia, both located in the prosoma.…”
Section: Introductionmentioning
confidence: 98%
“…Following fine work of the arachnid CNS (Babu, 1975), several other workers (Babu, 1985;Babu & Barth, 1984;Doeffinger et al, 2010;Hill, 2006;Hwang & Moon, 2003;Park et al, 2013;Weltzien & Barth, 1991;Weygoldt, 1985) have reported structural organization of the CNS of arthropod animals. However, most of our anatomical and histological understandings of Opilione CNS comes from only a few authors (Shultz & Pinto-da-Rocha, 2007).…”
Section: Introductionmentioning
confidence: 99%